Validation and Prioritization of Design Options for Accessible Player Experiences. Issue 6 (20th June 2022) - Power, Christopher; Cairns, Paul; Barlet, Mark; Haynes, Gregory; Beeston, Jen; DeHaven, Triskal
Abstract: The profile of accessible design of digital games has increased rapidly in both research and practice. Whereas at one time accessibility was a niche area of interest, it is now a key feature promoted in commercial gaming. Typically, games achieve accessibility by offering a range of options, both in settings and gameplay, that players can customize to meet their individual needs and preferences. However, there is a distinct lack of systematic data regarding the accessibility options that players prefer, how options can be prioritized in design or how options can impact player experience. This paper presents a study that collects data about options preferred by players and uses it to expand and validate a design vocabulary for accessible design in games. Further, the results point to a need to prioritize particular types of options, specifically those relating to the player-feedback loop of games, before implementing options that modify the challenges encountered by players.